Sacred Psychotherapy in the “Age of Authenticity”: Healing and Cultural Revivalism in Contemporary Finland - James M. Wilce (Religions, 2011)
Like other European countries, contemporary Finland has witnessed an explosion of healing modalities designatable as “New Age” (though not without profound controversy, [1]). This paper focuses on Finnish courses in lament (wept song, tuneful weeping with words) that combine healing conceived along psychotherapeutic lines and lessons from the lament tradition of rural Karelia, a region some Finns regard as their cultural heartland. A primary goal of the paper is to explicate a concept of “authenticity” emerging in lament courses, in which disclosing the depths of one’s feelings is supported not only by invoking “psy-“ discourses of self-help, but also by construing the genuine emotional self-disclosure that characterizes neolamentation as a sacred activity and a vital contribution to the welfare of the Finnish people.